2022
DOI: 10.1007/s10853-022-07630-w
|View full text |Cite
|
Sign up to set email alerts
|

Sintering condition-dependent electromechanical behavior of the lead-free piezoelectric Bi1/2K1/2TiO3

Abstract: Sintering conditions govern the optimized functional properties of ceramics. However, solid-state processing of Bi1/2K1/2TiO3 (BKT), an important end member for lead-free piezoelectric solid solutions suitable for higher temperature (≤ 300 °C) transducer applications, is challenging due to the low melting temperature (≈1070 °C). In this work, the sintering temperature (1030 °C, 1050 °C, and 1060 °C) and dwell time (10 h, 20 h, and 40 h)-dependent functional properties of solid-state processed BKT were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…The dielectric response of the sample cooled with 5 K min −1 rate (NC 900 ) (Fig. 2a) matches well with that of previously reported as-processed KBT ceramics, 27,40 indicating 5 K min −1 cooling from 900 °C does not signicantly inuence the dielectric response of KBT. The NC 900 sample exhibits a relatively high maximum dielectric permittivity of 4500 at the temperature of maximum permittivity, T m of 378 °C at 1 MHz, where T m varies with measurement frequency.…”
Section: Inuence Of Cooling Rate and Maximum Temperature On The Anne...supporting
confidence: 89%
See 4 more Smart Citations
“…The dielectric response of the sample cooled with 5 K min −1 rate (NC 900 ) (Fig. 2a) matches well with that of previously reported as-processed KBT ceramics, 27,40 indicating 5 K min −1 cooling from 900 °C does not signicantly inuence the dielectric response of KBT. The NC 900 sample exhibits a relatively high maximum dielectric permittivity of 4500 at the temperature of maximum permittivity, T m of 378 °C at 1 MHz, where T m varies with measurement frequency.…”
Section: Inuence Of Cooling Rate and Maximum Temperature On The Anne...supporting
confidence: 89%
“…Therefore, the origin of such an increase is not known; however, a relative change in structure distortion and extrinsic domain wall contributions could play a role here. Our previous work 40 on the stress-amplitude-dependent Rayleigh analysis of KBT revealed that the temperature-dependent relative change of intrinsic and extrinsic contributions to the overall piezoelectric coefficient can differ depending on the variation in tetragonal distortion of the as-processed sample. Nevertheless, further investigation of the variation in tetragonal distortion by in situ temperature-dependent diffraction measurement will be required to understand this.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations